Association of retinal microvascular abnormalities and neuromyelitis optica spectrum disorders with optical coherence tomography angiography - Guo, Jiaqi; Zhang, Dan; Gong, Yan; Liu, Jiang; Zhang, Jiong; Zhao, Yitian (Frontiers in Neuroscience, 2023)
Neuromyelitis Optica (NMO) is an extremely disabling auto-immune central nervous system disease caused by the abnormal attack of the immune system on glial cells and neurons. One of the signs of NMO is unilateral or bilateral optic neuritis (ON). It is worth noting that the onset of NMO often starts in the unilateral eyes, and the retina of both eyes may be involved in the later stage of disease development, resulting in visual loss. Therefore, ophthalmic imaging examination using optical coherence tomography angiography (OCTA) can be potentially useful for the early diagnosis of NMO and may provide a time window for the prevention of the malignant development of diseases. To study the retinal microvascular changes of NMO, we collected 25 OCTA images from 22 NMO patients and 50 OCTA images from 25 healthy subjects. By applying effective retinal microvascular segmentation and foveal avascular zone (FAZ) segmentation techniques, we obtain the key OCTA structures for biomarker analysis. We use specifically designed methods to extract 12 microvascular features from the segmentation results. Afterwards, we classify the OCTA images of NMO patients into the ON AND non-ON groups according to whether they had optic neuritis. Both groups are separately compared with the healthy control (HC) group. The statistical results show that in the non-ON group, the FAZ presents shape changes in the deep layer of the retina. There is no significant microvascular difference between the non-ON and HC groups. However, the ON group presents microvascular degeneration in both superficial and deep retinal layers. By incorporating the sub-regional analysis, we can see that the pathological variations mainly occur in the ON side, particularly within the internal ring close to the FAZ.